(untitled) (Praxis Educativa, 2026)
This article starts with the school, teaching and research territories involved in pedagogical social movements in the face of cognitive/academic capitalism, as referents of the places of enunciation that debate monological conceptions in research and training. Next, lines of reflection are drawn from our research careers, to focus and develop nodes-axes on the epistemic turns: decolonizing, post-humanist and ontological. It seeks to understand the idea of humus-Earth-humanity as a sustenance that configures the constructs developed around other ways of researching in a communal horizontality from the Bio/Geo/Pedagogies, as a necessary epistemic field. Underlying this journey are a series of theses such as the simultaneity and epistemic stripping of critical perspectives in research; to decant in turn the proposal to understand the cosmopolitical perspective of epistemic pluralism from the horizon of a situated ontologization of and in educational and pedagogical research.